In Memoriam Professor Andrzej Orłowski (1947–2020) - NOWICKI, Andrzej; STĘPNOWSKI, Andrzej (Archives of Acoustics, 2020)
Professor Andrzej Orłowski, a long-time employee of National Marine Fisheries Research Institute, passed away on October 27, 2020. He was an outstanding scientist in the field of hydroacoustics. Inventor of the method of use of multiple echo measurements to assess the type of the seabed. To this day, this method is called the Orłowski Method. Professor Orłowski was a member of the Physics Section of the SCOR, the NMFRI Scientific Council, the Polish Acoustical Society, ICES Fishery Acoustic Science and Technology Group, ICES Fish Technology and Fish Behavior Working Group, ICES SG Acoustic Seabed Classification and ICES SG Fish Avoidance of Research Vessels.